High‐voltage p‐type PERC solar cells with anchored plating and hydrogenation. (25th January 2018) - Ciesla, Alison; Chen, Ran; Wang, Sisi; Ji, Jingjia; Shi, Zhengrong; Mai, Ly; Chan, Catherine; Hallam, Brett; Chong, CheeMun; Wenham, Stuart; Green, Martin
Abstract: A common concern regarding plated contacts to solar cells is the adhesion strength. In this work, laser‐formed anchor points have been applied to Suntech Power's PLUTO passivated emitter and rear cells. Voltages as high as 696 mV have been achieved, showing the ability of a laser‐doped selective emitter at the front surface and localized contacts at the rear when combined with the hydrogenation of defects to reduce the device dark saturation current to well below current norms for commercial passivated emitter and rear cells. The simple hydrogen passivation process applied during sintering appears to facilitate the high voltages by significantly reducing recombination associated with the p‐type Cz wafer and laser‐induced defects formed during laser doping. The same hydrogenation process almost entirely eliminates the damage caused by laser ablation in forming the anchor points. With 50% anchor point coverage (more than necessary for adhesion equivalent to or stronger than screen‐printed contacts), an average VOC of 693 mV was achieved, with an average current of 40.5 mA/cm 2, average device efficiency of 20.2%, and a single best cell of 20.5% efficiency. These cells also exhibit excellent contact adhesion and pass all thermal cycling and damp‐heat testing according to IEC 61215. Abstract : Open‐circuit voltages (VOC ) of 696 mV have been achieved on plated p‐type passivated emitter and rear cells using p‐type industrial‐Cz wafers. This was achieved by combining a laser‐doped selective emitter at the front surface, localized contacts at the rear, and hydrogenation of defects to reduce the device dark saturation current to well below that for typical passivated emitter and rear cells. Laser‐formed anchor points have been included to ensure excellent contact adhesion that matches that of screen‐printed cells while maintaining an average VOC of 693 mV.